A Comparative Analysis of Arabic and English Literacy in Islamic and Public Universities: Perspectives of Students and Lecturers - Safii, Randi; Daud, Devika Rahayu; Doni, Chaterina Puteri (Assuthur: Jurnal Pendidikan Bahasa Arab, 2025)
This study is entitled A Comparative Analysis of Arabic and English Language Literacy in Islamic and General Universities: Students' and Lecturers’ Perspectives . It aims to compare the literacy conditions of Arabic and English in two types of universities and identify perceptions, teaching strategies, and factors influencing language proficiency from students' and lecturers’ perspectives. The research employed a qualitative approach with a comparative case study design, involving in-depth interviews, classroom observations, and document analysis at two higher education institutions. Participants included 12 students and 6 lecturers. Findings revealed significant differences in motivation, usage practices, and language policy between the two university types. Students at Islamic universities showed greater focus on Arabic, while those at general universities prioritized English. However, both groups faced similar challenges in active language production. Recommendations are provided to improve teaching strategies and align language policy implementation.